2004
DOI: 10.1002/clc.4960270404
|View full text |Cite
|
Sign up to set email alerts
|

Role of noninvasive studies in risk stratification for sudden cardiac death

Abstract: Summary: Sudden cardiac death (SCD) is one of the leading causes of mortality in developing countries. To prevent SCD, it is crucial to have effective tools for identifying patients at risk, given that there are now effective devices and medications that can prevent SCD. Two noninvasive electrocardiographic tools have been approved by the Food and Drug Administration and are being used clinically for identifying patients at risk for SCD: the signal-averaged electrocardiogram (SAECG) and T-wave alternans (TWA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Sudden cardiac death, one of the leading causes of mortality, remains a health problem of epidemic proportions. [ 13 14 ] Ventricular arrhythmias, the most important causes of sudden cardiac death, are common in hypertensive patients. The underlying mechanisms are: left ventricular hypertrophy (LVH), myocardial ischemia, and impaired left ventricular function.…”
mentioning
confidence: 99%
“…Sudden cardiac death, one of the leading causes of mortality, remains a health problem of epidemic proportions. [ 13 14 ] Ventricular arrhythmias, the most important causes of sudden cardiac death, are common in hypertensive patients. The underlying mechanisms are: left ventricular hypertrophy (LVH), myocardial ischemia, and impaired left ventricular function.…”
mentioning
confidence: 99%
“…6 Previous studies indicated higher risk with greater LVWT, especially with extreme hypertrophy >30 mm, but patients with mild left ventricular hypertrophy (LVH) are not event free. 7-9 Thus, morphological measures of LVH appear insufficiently characterized to effectively translate into risk stratification strategies.…”
mentioning
confidence: 99%